1996
DOI: 10.1074/jbc.271.37.22791
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of a Mutant Secretory Protein, α1-Antitrypsin Z, in the Endoplasmic Reticulum Requires Proteasome Activity

Abstract: Degradation of proteins that are retained in the quality control apparatus of the endoplasmic reticulum (ER) has been attributed to a third proteolytic system, distinct from the lysosomal and the cytoplasmic ubiquitindependent proteosomal proteolytic pathways. However, several recent studies have shown that ER degradation of a mutant membrane protein, CFTR⌬F508, is at least in part mediated from the cytoplasmic side by the 26 S proteasome. In this study, we examined the possibility that ER degradation of mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
236
1
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 346 publications
(247 citation statements)
references
References 26 publications
8
236
1
2
Order By: Relevance
“…[16][17][18] It is still not clear how the ATZ is transported from the lumen of the ER to the proteasome in the cytoplasm. Although retrograde translocation through the microsomal import channel has been proposed for some ER proteins, there is growing evidence for a mechanism in which the proteasome, as part of a multiprotein complex that forms a platform on the cytosolic side of the ER membrane, directly mediates extraction of substrates from the ER membrane.…”
Section: The Proteasomal and Autophagic Pathways Contribute To Disposmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] It is still not clear how the ATZ is transported from the lumen of the ER to the proteasome in the cytoplasm. Although retrograde translocation through the microsomal import channel has been proposed for some ER proteins, there is growing evidence for a mechanism in which the proteasome, as part of a multiprotein complex that forms a platform on the cytosolic side of the ER membrane, directly mediates extraction of substrates from the ER membrane.…”
Section: The Proteasomal and Autophagic Pathways Contribute To Disposmentioning
confidence: 99%
“…Although retrograde translocation through the microsomal import channel has been proposed for some ER proteins, there is growing evidence for a mechanism in which the proteasome, as part of a multiprotein complex that forms a platform on the cytosolic side of the ER membrane, directly mediates extraction of substrates from the ER membrane. 19,20 Nevertheless, these early studies in yeast, mammalian cell lines and cell-free systems all indicated that the proteasomal pathway could not fully account for disposal of ATZ [16][17][18][21][22][23] -that is in the absence of proteasomal activity there was clear-cut residual and time-dependent degradation of ATZ.…”
Section: The Proteasomal and Autophagic Pathways Contribute To Disposmentioning
confidence: 99%
“…Studies in many systems have indicated that the proteosomal system is involved. [17][18][19][20][21] This involvement appears to include both the classical ubiquitin-dependent proteosomal mechanism as well as a ubiquitin-independent proteosomal mechanism. 19 However, exactly how ␣1ATZ on the luminal side of the ER membrane is accessed by the proteosome from the cytoplasm is not clear.…”
Section: Degradation Of Mutant ␣1atz In the Ermentioning
confidence: 99%
“…For instance, interaction with the molecular ER chaperone BiP (binding protein) appears to be necessary for the retrograde transport and proteasomal degradation of soluble proteins such as mutant yeast carboxypeptidase ysc Y (Plemper et al, 1997) but not for that of polytopic membrane proteins such as the mutant ATP-binding cassette transporter Pdr5* . In the same line, interaction with calnexin, another ER chaperone, facilitates the degradation of the soluble mutant ␣1-anti-trypsin Z (Qu et al, 1996) and prepro-␣ factor (McCracken and Brodsky, 1996) but is not important for the degradation of the polytopic cystic fibrosis conductance regulator (CFTR) . On the other hand, soluble and membrane proteins may share common mechanisms for recognition and targeting to proteasomal degradation.…”
Section: Introductionmentioning
confidence: 99%